Strategies promoting psychological well-being of students: a case study and accounting games - Khinkanina, Natalia (My University, 2023)
The article provides a rationale for the importance of students' psychological well-being in the process of acquiring knowledge and the role of teachers in its formation. Proposed practical recommendations for successful and entertaining study of the material at different stages of the accounting course.
СТРАТЕГИИ, СПОСОБСТВУЮЩИЕ ПСИХОЛОГИЧЕСКОМУ БЛАГОПОЛУЧИЮ СТУДЕНТОВ, НА ПРИМЕРЕ ПРЕПОДАВАНИЯ КУРСА «БУХГАЛТЕРСКИЙ УЧЁТ»
Keywords: psychological well-being; students; accounting